'Brazil, Tell Me How It Feels': Soccer, Music, Narcissism, and the State, or Mascherano's Failure. Issue 2 (2nd April 2016) - Alabarces, Pablo
Abstract : During Brazil's 2014 World Cup finals, Argentine fans popularized a chant that stated "Brazil, tell me how it feels". The chant became viral, and produced a Brazilian response, "Argentina, me diz que se sente": both discussed relationship of rivalry by joking at the other's expenses. But it was surprising that the chant was based on the melody of a very old song from the American rock band Creedence Clearwater Revival, recorded in 1969, possibly before the birth of those who sang the melody in Brazil ("Bad Moon Rising", a very popular song recorded many times). This paper discusses several topics derived from that fact: the relationship between popular music and football chants; the uses of popular music and global pop at the World Cups from 1962 to our days; the self-presentation of the "local" (national) fans before a globalized media scene; and, last but not least, the role of sport icons and heroes for the fans but also for the construction of national epics (the icons and heroes invoked in the chants included, obviously, both Maradona and Messi, two of the most important football heroes from the '80s until today). The core idea is to show how contemporary football culture must be described and interpreted in the continuous intersection of local texts -and fans' practices- and global events.